Bioimpedance assessment of body composition in the first adulthood period of somatic types residing in highland - Kozuev Kadyr; Tulekeev Toktogazy; Dzholdubaev Sagynbek; Toichieva Zarina; Abdullaeva Zhypargul (Journal of Electrical Bioimpedance)
The current stage of development of medical science is characterized by growing interest in constitutional typology and clinical anthropology. The anatomical-anthropological approach is an integrative technique of biology and medicine that allows us to determine the criteria for normality and pathology of a person. Purpose of the study: comparative bioimpedance assessment of somatic types of body component composition among the first mature age period people residing in highland. Study design: a comparative bioimpedance assessment of body types according to the Heath and Carter’s scheme was performed to identify somatic types and body weight composition in healthy men of the 1st adulthood period living in high mountains (2469–3325 m above sea level). Somatotypical features of body composition have been established. An intertype and correlation analysis of body composition was conducted in individuals with different body types. Results: comparative bioimpedance and correlation analyses revealed differences in body composition indicators depending on population, age, body types and living conditions. Conclusion: mesoectomorphy, balanced ectomorphic, central and meso-endo types prevailed among the somatotype subgroups.